Regulating Dispute Resolution: ADR and Access to Justice at the Crossroads - Steffek, Felix (EBL-Schweitzer, 2013)
Cover; Preliminary Pages; Preface; Contents Summary; Detailed Contents; Contributors; Abbreviations; Part 1: Fundamental Issues; 1. Guide for Regulating Dispute Resolution (GRDR): Principles; 2. Guide for Regulating Dispute Resolution (GRDR): Principles and Comments; 3. Principled Regulation of Dispute Resolution: Taxonomy, Policy, Topics; Part 2: Regulation of Dispute Resolution; 4. Regulation of Dispute Resolution in Austria: A Traditional Litigation Culture Slowly Embraces ADR; 5. Regulation of Dispute Resolution in Belgium: Workable Solutions?